(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the characteristics of sexual disorder (F52) in female patients with generalized anxiety disorder at the National Institute of Mental Health. Research methods: A cross-sectional descriptive study was conducted on 141 female patients with generalized anxiety disorder who received outpatient and inpatient treatment at the National Institute of Mental Health, Bach Mai Hospital from September 2025 to April 2026. Results: In our study, the mean age of patients was 43.0±10.1 years, the majority were premenopausal (59.6%), and the mean age of starting sexual activities was 22.1±2.8 years. Common sexual disorders in the study participants included lack or loss of sexual desire (69.5%), orgasmic dysfunction (66,7%) and lack of sexual enjoyment (63.1%). Conclusion: Sexual disorder is highly prevalent among female patients with generalized anxiety disorder. Early detection, comprehensive assessment, and timely support for sexual disorder are crucial steps in the holistic treatment of patients with generalized anxiety disorder.